Acute respiratory infections hamper training and competition in cross-country skiers, especially in those with asthma - Mäki-Heikkilä, Rikhard; Karjalainen, Jussi; Parkkari, Jari; Huhtala, Heini; Valtonen, Maarit; Lehtimäki, Lauri (International journal of circumpolar health, 2023)
Acute respiratory infections (ARinf) are one of the leading causes that prevent athletes from training and competing. The aim of this study was to investigate the burden of ARinfs during one season among cross-country skiers. All Finnish cross-country skiers enrolled in the largest national competitions in winter 2019 (n = 1282) were sent a postal questionnaire. A higher proportion of skiers with than without asthma had to refrain from competitions because of ARinf (76.9% vs. 62.2%, p = 0.011) but there was no significant difference in refraining from training (91.2% vs. 83.8%, p = 0.084). In skiers with asthma, the median duration of a single ARinf episode was longer (5.0 days, IQR 3.8-6.8 vs. 4.0 days, IQR 3.0-6.7, p  = 0.017), and they had more days of absence because of ARinf throughout the season (median 15 days (IQR 8-28) vs. 10 days (IQR 6-18), p  = 0.006) in comparison to non-asthmatics. However, many of the skiers either trained (54.4%) or competed (22.5%) during an ARinf.